2018
DOI: 10.1002/fee.1764
|View full text |Cite
|
Sign up to set email alerts
|

Tropical mountain passes are out of reach – but not for arboreal species

Abstract: According to a prevailing hypothesis, lowland tropical organisms are unlikely to successfully cross mountain passes because they have neither acclimated nor adapted to the colder temperatures found at higher elevations. However, this expectation assumes that changes in temperature are uniform across space and fails to account for the presence of diverse microclimates created by structurally complex ecosystems, such as rainforests. We collected and analyzed temperature data from Afrotropical, Indomalayan, and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 68 publications
6
23
2
Order By: Relevance
“…Our findings contribute to reconcile contrasted views about the relative importance of two distinct scales of climate variability in shaping patterns of subterranean biodiversity (Zagmajster et al, ), a topic that has been recently discussed also in surface ecosystems (Scheffers et al, ; Scheffers & Williams, ). Using correlative methods, Zagmajster et al () and Eme et al () showed that long‐term temperature variability accounted for a substantial variation in range size of groundwater crustaceans across Europe.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings contribute to reconcile contrasted views about the relative importance of two distinct scales of climate variability in shaping patterns of subterranean biodiversity (Zagmajster et al, ), a topic that has been recently discussed also in surface ecosystems (Scheffers et al, ; Scheffers & Williams, ). Using correlative methods, Zagmajster et al () and Eme et al () showed that long‐term temperature variability accounted for a substantial variation in range size of groundwater crustaceans across Europe.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings contribute to reconcile contrasted views about the relative importance of two distinct scales of climate variability in shaping patterns of subterranean biodiversity (Zagmajster et al, 2014), a topic that has been recently discussed also in surface ecosystems (Scheffers et al, 2017;Scheffers & Williams, 2018).…”
Section: Climatic Controls On Subterranean Biodiversity Patternssupporting
confidence: 76%
“…Our hypothesis is derived from the same underlying physiological principle; species are adapted to temperatures normally encountered in their temporal and geographical habitat or microhabitat (Janzen, ). Similar hypothesis has been proposed for a vertical climatic gradient in rain forest (Scheffers & Williams, ), and circadian climatic gradients with contrasting daytime and night‐time thermal variability (Muñoz & Bodensteiner, ).…”
Section: Introductionsupporting
confidence: 76%
“…Local climatic fluctuations, such as habitat variation, may also explain the absence of the expected divergence in dispersal capacity (see Chan et al., ). It is possible that horizontal movements of organisms will represent a climate sorting process allowing organisms to increase resilience to climatic changes under current upcoming heating as is proposed in the analogous vertical climatic variation within tropical forest (Scheffers & Williams, ; Scheffers et al., ). Habitat‐driven thermal variation may exceed the expected rise of temperatures, and thermally buffered habitats can become climatic shelters for the organisms most exposed to the thermal shocks (see Lenoir & Svenning, ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, verticality infers greater persistence to climatic instability (Davison and Chiba 2008, Scheffers et al 2013, Scheffers and Williams 2018. Vertical movements, either upwards in the canopy or downwards into the ground, afford more plastic ecologies and confer advantages over entirely ground-dwelling species due to a greater accessibility to micro-habitats and climates.…”
Section: Introductionmentioning
confidence: 99%